MODERN RESIDENTIAL COMPLEXES IN THE CITIES OF UZBEKISTAN (British Journal of Global Ecology and Sustainable Development, 2023)
This article explores the features and benefits of modern residential complexes in the cities of Uzbekistan. With the growing demand for high-quality housing and the government's efforts to promote urban development, modern residential complexes have become a popular housing option for residents in Uzbekistan. Through a comparison with traditional housing options and an analysis of the unique features and advantages of modern residential complexes, this article provides insights into the potential impact of these complexes on the urban development of Uzbekistan.